Research on the Parametric Modelling Approach of Vortex Generator on Wind Turbine Airfoil - Chen, Ming; Zhao, Zhenzhou; Liu, Huiwen; Wang, Tongguang; Meng, Lingyu; Feng, Junxin; Jiang, Ruifang; Wang, Dingding (Frontiers in Energy Research, 2021)
Counter-rotating vortex generators (VGs) are typically employed to delay airflow separation on wind turbine blades. Large-size wind turbine blades equipped with small size VGs make the computational fluid dynamics (CFD) researches require a great deal of computational resources. Parametric models of VGs can effectively improve the numerical research efficiency of wind turbine blades with VGs. In order to improve the accuracy of such parametric models, this study proposed a series of modeling approaches to determine the positions of the adding source term in Cartesian coordinates, the VG vortex core radius, etc., on the wind turbine airfoils. These techniques are integrated with a maximum circulation algorithm by considering the interactions between VG pairs to predict the performance of a DU91-W2-250 blade section with VGs. The proposed parametric model and an entity model at different angles of attack (AoAs) are implemented on the blade section. Our approach is validated using experimental data. Comparisons demonstrate a strong agreement between the modelled and experimental results, proving the high accuracy of the two models. The numerical results of the models are then compared and analyzed at different incoming flow velocities and AoAs to verify the universality of the proposed parametric approaches. The results reveal a high consistency between the vortex structure, the velocity profile above the blade surface and the distribution of the pressure coefficient calculated by the two models. This proves the high universality of the proposed approaches and demonstrates the potential of the parametric model in replacing the VG entity model. The VG parametric model expresses VG parameters by program, which can improve the research efficiency of VG arrangement on wind turbine blades.